(untitled) (Ameghiniana, 2013)
SPECIES OF ATMODESMINAE (BIVALVIA) FROM THE LATE PALEOZOIC OF PATAGONIA Two new bivalve species of the Atomodesminae are described and figured. They belong to the middle and upper strata of Las Salinas Formation, ranging from Middle Carboniferous to Lower Permian? in age. The available specimens are fragrnentary and partly deformed by compression. Although incomplete information could be obtained, they are provisionally assigned to the Permian genus Atomodesma Beyrich.